Effect of Pasteurization Temperature on the Quality of Goat Cheese - Gutung, Smita; Sah, Baidya Nath Prasad (Journal of Food Science and Technology Nepal, 2014)
The research was carried to study quality and yield of goat cheese by varying pasteurisation conditions; 63°C for 30min (Sample A), 80°C for 10min (Sample B) and 90°C for 60sec (Sample C). Titrable acidity, pH, moisture, fat, protein and ash, total plate count, Coliform count of goat milk, cheese samples A, B, and C were measured. There were fat recoveries of 67.23%, 67.72%, and 70.15% while protein recoveries of 71.15%, 66.88, and 69.32 respectively in the samples A, B, and C. The samples A, B, and C had moisture content of 59.72%, 63.15%, and 64.3%. The samples were subjected to sensory evaluation in term of color, flavor, texture, taste and overall acceptability on a 9-point hedonic rating scale. The data obtained were analysed statistically (p<0.05). Sample C was ranked the best. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10616 J. Food Sci. Technol. Nepal, Vol. 7 (93-97), 2012